Who Is The Ultimate Planning Authority In Malaysia? Reviewing The Powers And The Role Of The Appeal Board - Khaw, Lake Tee (Journal of Malaysian and Comparative Law, 2019)
The Federal Constitution perscribes that town and country planning is a shared responsibility of the Federal and State Governments. The planning law in 1976 originally defined three levels of planning authorities all of them at the State level. This was expanded in 2001 to include a National as well as regional planning authorities. However, the quasi-judicial planning Appeal Board which is appointed by the State Government appears to be the ultimate authority since its decision is final and there is no power for the State or Federal governments to intervene. The Board is an innovation ahead of its time but its constitution lacks representation in relevant areas of expertise, power is concentrated on the Chairman and there are no apparent constrains on the scope and powers of the Board. A review of 12 years experience suggests that a restructing of the Board should be carried to be more inclusive in its decision-making process. Its mandate and duty should be to protect environmental resources and public good rather than to serve private interests.